Female Transformational Leadership and Imposter Syndrome Mitigation in Traditionally Male-Dominated Industries - Ramesh, Karisma (Digital Repository of Theses, 2024)
Imposter syndrome (IS) presents a significant barrier to the advancement of women in traditionally male-dominated industries, perpetuating a culture of exclusion and hindering progress towards gender parity in leadership roles. This study investigates the causes, effects, and potential solutions of IS among female workers in male-dominated sectors, focusing on themes identified through interviews with a cohort of female leaders and workers. Through a multi-case study design, the research explores the experiences of women in various male-dominated industries, revealing pervasive themes such as gender imbalance, gender bias, and a lack of female representation in leadership positions contributing to feelings of IS. Participants reported instances of being undervalued, overlooked, and invalidated by a predominantly male leadership, exacerbating feelings of professional inadequacy and hindering career progression. Despite these challenges, participants offered valuable insights and recommendations for combating IS in the workplace. Strategies suggested included establishing support networks, promoting open and transparent discussions about IS, fostering inclusivity and equality, implementing an open-door policy, providing training and development programs for both men and women, and encouraging mentorship opportunities. Mentorship emerged as a particularly effective tool for providing resilience and combating IS, with female mentors playing a crucial role in inspiring confidence and guiding career trajectories in male-dominated industries. The findings underscore the importance of transforming organizational cultures to promote diversity, equity, and inclusion, thus creating environments where women feel supported, valued, and empowered to overcome the barriers posed by IS. Overall, this study contributes to a deeper understanding of the complexities surrounding IS in traditionally male-dominated industries and offers practical strategies for fostering a more inclusive and supportive workplace environment conducive to the advancement of women into leadership positions.